(untitled) (Journal of Geography and Environmental Management, 2017)
In this article development of ecological tourism in Kazakhstan is described. In article special attention is paid to problems of development of ecological tourism in especially protected natural territories of Kazakhstan. The simplest form of ecological tourism is the travel «among the nature». More developed form of ecotourism covers such spheres as fauna, plants, a variety of vital forms, stable types of economy, environmental protection, culture, heritage, society and the person. In other words, ecological tourism represents the important instrument of sustainable development of territories. In article the Australian model of ecological tourism which is directed to knowledge of the nature is considered. The analysis of ekologo-tourist capacity of Kazakhstan, formation of a tourist product and its advance on the market is carried out. Also an opredelan a role of ecological tourism in the tourist industry of Kazakhstan, the comparative analysis along with other types of tourism is carried out. Authors point to the significant and growing popularity of ecotourism in especially protected natural territories. Recommendations about advance of this direction of tourism in Kazakhstane.Prodvizheniya of this direction of tourism in Kazakhstan are made.